New phenolic halogenated disinfection byproducts in simulated chlorinated drinking water: Identification, decomposition, and control by ozone-activated carbon treatment. (1st December 2018) - Huang, Yan; Li, Huan; Zhou, Qing; Li, Aimin; Shuang, Chendong; Xian, Qiming; Xu, Bin; Pan, Yang
Abstract: Recently, 13 new phenolic halogenated disinfection byproducts (DBPs) were discovered and confirmed in chlorinated drinking water using ultra performance liquid chromatography/electrospray ionization-triple quadrupole mass spectrometry (UPLC/ESI-tqMS), which have been attracting a growing concern due to their higher chronic cytotoxicity, developmental toxicity, and growth inhibition compared with commonly known aliphatic DBPs. In this study, another 12 new phenolic halogenated DBPs were detected and identified in simulated chlorinated drinking water samples, including two monohalo-4-hydroxybenzaldehydes, two monohalo-4-hydroxybenzoic acids, three monohalo-salicylic acids, and five mono/di/trihalo-phenols. Decomposition mechanisms of these new phenolic halogenated DBPs during chlorination were speculated and partially verified by identifying intermediate products. These new DBPs could undergo hydrolysis, halogenation, substitution, addition, decarboxylation, and rearrangement reactions to form a series of decomposition products, including dihaloacetic acids, 2-halomaleic acids, and a group of new heterocyclic DBPs (trihalo-hydroxy-cyclopentene-diones). A bench-scale ozone-granular activated carbon (GAC) treatment unit was designed and set up in the lab. It was found that ozonation and GAC filtration were effective in reducing dissolved organic carbon levels and aromaticity (DBP precursors) of simulated raw water samples, and thus were effective in decreasing the concentrations of these new phenolic DBPs by 82.5% and 88.6%, respectively. Furthermore, four different treatment scenarios (i.e., ozonation, GAC filtration, ozonation followed by GAC filtration, and GAC filtration followed by ozonation) were evaluated and compared. Results showed that ozonation followed by GAC filtration was most effective in precursor removal and could decrease the level of these new phenolic DBPs by up to 97.3%. Graphical abstract: Highlights: Twelve new phenolic halogenated DBPs were identified in chlorinated drinking water. Decomposition pathways in chlorination were proposed and partially verified. O3 -GAC was an effective method for controlling these new phenolic DBPs.